Pengaruh Pemberian Biourine dan Dosis Pupuk Anorganik (N,P,K) Terhadap Beberapa Sifat Kimia Tanah Pegok dan Hasil Tanaman Bayam (Amaranthus sp.) - NI KADEK SHINTA DHARMAYANTI; A.A. NYOMAN SUPADMA; I DEWA MADE ARTHAGAMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2013)
ABSTRACT The Effect of Biourine and Dosage of Inorganic Fertilizer (N,P,K) to Several Chemical Properties of Soil Pegok and the Yield of Spinach Plant (Amaranthus sp.) The research aims to find out the effect of interaction between Biourine and dosage of inorganic fertilizer (N,P,K) and to find out the ability of Biourine in reducing the use of inorganic fertilizer (N,P,K) towards several chemical properties of Pegok soil and the yield of spinach plant (Amaranthus sp.). The research was conducted on November 2012 until January 2013 at the green house of Pegok’s Experimental Garden in Denpasar, and at Soil Laboratory, Faculty of Agriculture, Udayana University. The experiment used Randomized Block Design (RBD) with two factors, including  Biourine concentration (U) and dosage of inorganic fertilizer (P). The observation parameters of this research were total N, available P, available K, C-organik of soil, the pH of the soil and the growth and the quality of the plants, which include the height of the plants, the weight of the fresh shoots, oven dried weight of shoots, the total weight of the roots, oven dried weight of roots. The result of the statistic analysis shows that the Biourine and dosage of inorganic fertilizer is not affecting all parameters observed. The use of the Biourine obviously affects all of the parameters except the available P, the pH of the soil and oven dried weight of roots. More over, the use of the dosage of inorganic fertilizer affects all parameters except which include the height of the plants the acidity of the soil is obviously affecting, and also for other parameters are not affecting.   Key words : Biourine, inorganic fertilizer, spinach plant